Middle Passage: In the Absence of Detail, Presenting and Representing a Historical Void - Walcott, Rinaldo (Kronos: Southern African Histories, 2020)
What might it mean to imagine the Middle Passage? What work does imagining the Middle Passage do? Despite its centrality in invocations of transatlantic slavery, representations of the Middle Passage are few. By representations of the Middle Passage, I mean artistic representations across literature, film, music, and visual art that seek to offer imaginative insights into its horrors. M. NourbeSe Philip’s 2008 long poem, Zong! not only documents the murder of some 150 Africans aboard the slave ship from which the poem takes its name, it does something more. The poetics of Zong! enacts those that have gone missing, and thus emerges into a void to place into evidence that which we assumed we had lost. The work of imagination in the poem replaces that which we might think had gone missing prior to its poetic representation. Through reworking and reordering the legal decision in the 1783 court case, Gregson v. Gilbert,1 Philip’s poem recounts the story of the slave ship Zong. The poem re-presents the evidence of the mass murder in the voice of those we might otherwise not hear in such legal documents, in this instance that of Setaey Adamu Boateng. Philip shares authorship of Zong! with Setaey Adamu Boateng, who she tells us guided her and aided her in the recovery and creation the story of the Zong. In this case then, Zong! also exceeds the poem as a form and genre, and even as an event in the proper use of that term. To do so, Philip must break language and break with language. The very page, the architecture of each page of the poem spatialises the break with language, and its representation on the page, as one of voids and or missingness, and simultaneously fills those gaps with knowledge, with untold history, with people and lives that would otherwise remain unknown. Philip’s Zong! is a poem that is a sort of return, but a return, too, brings with it the problem of the missing, the problem of the void. It is a poem that requires us to think the Atlantic Ocean differently and anew.